Keywords generation algorithm based on bipartite graph - Yang, Yan; Zhu, Jing-Hua; Jin, Hu; Li, Wei (Tongxin Xuebao, 2011)
To improve the efficiency of keywords generation, a bipartite graph based keywords generation(BGKG) algorithm was proposed. It generated keywords based on search engine logs and built a bipartite graph between query terms and the clicked URLs. It took into account the rank of the URLs in result pages and the order of users' clicking. Experiments were done with real query logs. The results show that keywords generated by BGKG can satisfy the needs of enterprise clients and BGKG is more efficient than other keyword generation algorithms.